(untitled) (International Journal of Food and Nutritional Sciences, 2021)
The present study aims to prepare an analytical study of empowerment of women in Panchayatiraj System in Assam. The present study explores the main focused on the nature and concept of Panchayati Raj is deeply entrenched in the process of strengthening the basic democracy at the grass-roots level by ensuring people‟s participation in local governance and administration. Women in India now participate in all activities such as education, politics, media, art and culture, service sectors, science and technology, etc. The Constitution of India guarantees to all Indian women equality (Article 14), no discrimination by the State (Article 15(1)), equality of opportunity (Article 16), and equal pay for equal work (Article 39(d)). The method of investigation in the present study is descriptive survey method employed. The present study was conducted to an unexplored the social and economic problems experienced by senior women residing within the Gaon Panchayat limits of Kamrup district in Assam. The sample for the present study consisted of 112 women. The present investigation has broad in to light some interesting fact and a significant relationship existing between socioeconomic condition and women empowerment of the investigated. The findings of the present study revealed that majority of senior women were found to have severed health and financial problems and moderate level of problems in social, familial, emotional and psychological areas. Senior most women reflected the experience of more psycho-social problems as compared to their women. Assam Panchayat Act 1994, A three-tier system with Zilla Parishad has been introduced Gaon Panchayat, Anchalik Panchayat and Zilla Parishad.